Activity, movement and secretive behavior of a threatened arboreal folivore, the thin-spined porcupine, in the Atlantic forest of southern Bahia, Brazil - Fernandez Gine, Gaston Andres; Barbanti Duarte, Jose Mauricio [UNESP]; Senra Motta, Tatiana Cristina; Faria, Deborah (Wiley-Blackwell, 2012)
Activity and behavior patterns are important components of a given species ecological strategy, as they have profound implications for its survival and reproduction. Here, we studied the activities, movements and secretive behavior of the thin-spined porcupine Chaetomys subspinosus (Rodentia: Erethizontidae), a threatened arboreal folivore in the Brazilian Atlantic rainforest. We aimed to ascertain the behavioral strategies used by this species as well as its responses to seasonal and daily climatic changes. Four radio-collared individuals were followed continuously for 72-h in the summer and winter, as well as during 146 half-night sessions conducted from April 2005 to September 2006 in forest remnants in southern Bahia. The thin-spined porcupines were nocturnally active (17:30-05:40 h), with peaks in activity and movement from 19:00 to 20:00 h and 03:00 to 04:00 h. Animals followed a circadian rhythm of activity during both the summer and winter. During the diel cycle, porcupines spent 74% of their time resting, 14% feeding, 11% traveling and 2% performing other activities. Distance traveled during the diel cycle averaged 277.5 +/- 117.9 m sd. The mean movement rate during the night was 21.6 +/- 30.1 m/h sd. No significant changes in activity budget or daily distance traveled were observed between seasons, most likely in response to the low fluctuations in climatic conditions and food availability throughout the year in the study region. However, rainfall reduced the time that the animals spent on feeding activities and explained day-to-day differences in activity budgets. We also provide details about intraspecific interactions and defecation behavior. Our observations confirmed that thin-spined porcupines, similar to other folivorous species, present low activity levels and short daily movements, and have adopted various cryptic habits, such as nocturnality, a solitary lifestyle, the tendency to leave offspring alone most of the time and defecation in concealed latrines.
Keywords: activity pattern; arboreal folivore; Atlantic Rainforest; Chaetomys subspinosus; Circadian rhythm; porcupine; travel distance